Pemikiran Teologi Feminis Riffat Hassan dan Relevansinya terhadap Peran Laki-Laki dalam Isu Gender - Syaifullah Aji Trianto (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2024)
Abstract Through reflection on her own life experience as part of the Muslim community, Riffat Hassan points out the social facts about gender inequality that occur in the majority of people who embrace Islam and according to her this fact is contrary to the teachings of Islam itself which upholds equality and justice. Then to answer this problem, Riffat Hassan proposed the idea of feminist theology. In this article, the author will examine Riffat Hassan's thoughts on feminist theology and show the relevance of these thoughts to the role of men in gender issues. The results of the study show that, first, Riffat Hassan succeeded in revealing that the cause of gender inequality is the patriarchal culture that underlies the interpretation and thinking of Islamic teachings, for example shown through the preservation of the myth of Eve's creation from Adam's rib, which according to Riffat Hassan, this story has been used as the strongest legitimacy to illustrate male superiority over women. Secondly, the goal of feminist theology for Riffat Hassan is not only to liberate Muslim women, but also Muslim men, because both are victims of patriarchal culture. This is where the role of men in gender issues finds its relevance. Keywords: feminist theology, patriarchal culture, gender inequality, creation myths